The Properties of Glycophorin a Transmembrane Helices in Erythrocyte Asymmetric Membrane: A Molecular Dynamics Study (Journal of Atomic and Molecular Sciences, 2011)
We have performed an 80ns molecular dynamics (MD) simulation of human red blood erythrocyte asymmetric membrane model. The NAMD code and CHARMM27 force field were used. We have estimated some features of embedded Glycophorin A (GpA) protein and have discussed some important problems concerning the interaction between the protein and surrounding media. It is stated that the lipid environment and protein immediate neighboring lead to the changes in helix-helix association, as well as to the protein orientation. The interaction nature between protein and neighboring phospholipid chains are dominant forces governing to helix-helix association.
Keywords: Glycophorin A (GpA) protein; erythrocyte membrane; molecular dynamics simulation; helix-helix association.